Computed Tomography Findings of Mandibular Nutrient Canals. Issue 4 (August 2015) - Kawashima, Yusuke; Sekiya, Kotaro; Sasaki, Yusuke; Tsukioka, Tsuneyuki; Muramatsu, Teruaki; Kaneda, Takashi
Abstract : Introduction: The purpose of this study was to assess computed tomography (CT) findings of mandibular nutrient canals using CT images. Materials and Methods: We retrospectively analyzed the mandibular CT images of 194 consecutive patients. For image analysis such as canal prevalence, location, number, size, shape, and the CT value of nutrient foramina were determined using CT axial images of 0.5 and 3 mm slice thickness. Results: We revealed that the nutrient canals were seen 94.3% in the mandible, mostly seen in the anterior region. By location, nutrient canals were particularly seen between the central and lateral incisors. The mean number of nutrient canals was 2.7. The mean diameter of the nutrient foramen between the central and lateral incisors was 1.0 mm. In about 80% of the cases, foramina between the central and lateral incisors were ovoid. The mean CT value for the nutrient foramina between the central and lateral incisors was 411 HU. Discussion and Conclusions: Mandibular nutrient canals were ovoid shape, and the mean CT value was 411 HU. By preoperative knowledge of the position and anatomy of the mandibular nutrient canals, complications such as injury to the nutrient canals can be avoided.